50 years of regional integration in ASEAN. Issue 5 (20th October 2019) - Cuyvers, Ludo; Chen, Lurong; Lombaerde, Philippe De
ABSTRACT: This article offers a brief overview of the development of ASEAN in its 50 years of existence. It covers the early motivations and developments since the late 1960s, the acceleration of integration and creation of the ASEAN Free Trade Area in the 1990s, and – more recently – the development of the ASEAN Economic Community, the ASEAN Political-Security Community, and the ASEAN Socio-Cultural Community.